Tin-zinc bimetallic oxide as well as preparation method and application thereof
By preparing tin-zinc bimetallic oxide SnO2/ZnO nanospheres, and utilizing the heterojunction structure and low-temperature operating conditions, the selectivity and response time issues of hydrogen sensors were solved, achieving high-sensitivity and fast-response hydrogen detection.
Patent Information
- Application Number
- CN202511541152.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-27
- Publication Date
- 2026-01-13
AI Technical Summary
Existing hydrogen sensors suffer from poor selectivity for hydrogen, low sensitivity, and high operating temperature. Furthermore, the material particles are not uniform in size, have a large average particle size, and a small specific surface area.
By synergistically interacting tin source and zinc salt with dimethylimidazole at the molecular level to form a metal-organic composite precursor, the growth of nanospheres is controlled by an in-situ symbiotic mechanism. Combined with the work function and band structure of n-type semiconductor oxide SnO2/ZnO, a heterojunction with a moderate potential barrier is formed, enabling rapid response and low-temperature operation.
The prepared Sn-Zn-O sensor exhibits high sensitivity and fast response at low temperatures, with a response time of 1.29 s, a recovery time of 147 s, and a detection limit of 0.1 ppm. It is also low in cost, environmentally friendly and non-toxic, and suitable for the safe detection of low concentrations of hydrogen.
Smart Images

Figure CN121317855A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sensor technology, specifically a tin-zinc bimetallic oxide, its preparation method, and its applications. Background Technology
[0002] Hydrogen possesses high energy density, extremely low ignition energy, a wide explosion limit, and is colorless and odorless. Therefore, in the use of hydrogen, sensors must be used to detect its concentration in the air. Among commonly used hydrogen sensors, those based on semiconductor metal oxides offer advantages such as low cost, simple fabrication process, and high stability. However, using only a single metal oxide suffers from poor selectivity for hydrogen, low sensitivity, and high operating temperature.
[0003] To address the aforementioned issue of poor gas selectivity, other metal oxides can be added to form bimetallic oxides, thereby improving the sensitivity to hydrogen. For example, existing literature 1 (Mondal, Biplob, et al. "ZnO-SnO2-based composite type gas sensor for selective hydrogen sensing." Sensors and Actuators B: Chemical 194(2014):389-396.) prepared a ZnO-SnO2 hydrogen sensor by using a sol-gel method to prepare a precursor solution of zinc acetate and tin tetrachloride, followed by spin coating to prepare a thin film and annealing. Although this technical solution exhibits selectivity for hydrogen at 150°C and a gas concentration of 100 ppm, its response value is only 0.9. The reason for this technical problem is that the ZnO / SnO2 material prepared by this technical solution is a physical mixture of ZnO rods with a size range of 150-500 nm (micrometer-scale) and SnO2 particles with a size range of 50-90 nm (nanometer-scale). Due to the significant size difference between the two materials, the heterojunction formed at the contact surface is uneven and discontinuous, meaning that a continuous and highly dense heterojunction network cannot be formed. This results in some "short-circuit" paths for electrons during transmission, reducing the response.
[0004] Therefore, to address the low response value of the sensor to hydrogen, it is necessary to further adjust the morphology of the material, increase the number of active sites, and form a uniform and continuous conductive network to improve the material's sensitivity to hydrogen. For example, existing literature 2 (Qin, Yuxiang, et al. "SnO2-Co3O4 nanocomposite sensor: Achieving ultra-selective hydrogen detection in mixed gas environments." Sensors and Actuators B: Chemical 422(2025):136521.) prepared SnO2-Co3O4 nanospheres with rough surfaces and uniform sizes using a room temperature solvent method, achieving a response value exceeding 20 at 325℃ and 300ppm. However, the response time exceeded 4 seconds at a hydrogen concentration of 500ppm. The reason for the long response time is that although the SnO2-Co3O4 particles are at the nanoscale, the size of the main material ranges from 300 to 800 nm. During the diffusion process, gas molecules need to diffuse into the depths of the pores formed by the stacking of nanospheres and into the interior of the nanospheres themselves to react. Therefore, the large-sized nanosphere structure leads to a slower diffusion rate of the gas diffusion process, which is reflected in the long response time.
[0005] To simultaneously reduce response time, MOF-derived oxides can be introduced. Leveraging the unique structure of MOF materials, small particle size, high specific surface area, and porosity can be achieved, thereby reducing response time. For example, existing literature 3 (Wang, Zijian, et al. "Construction of ultra-sensitive hydrogen sensor based on two phases In2O3 nanoparticles modified by regular dodecahedral ZnO." Sensors and Actuators B: Chemical 420(2024):136422.) uses a solvothermal method and calcination to obtain ZnO-modified In2O3 with a regular dodecahedral morphology based on MOF materials, achieving a response time reduced to 1 second and a response value increased to 80. The core reason for the high sensitivity and fast response of this technical solution is the utilization of the dodecahedral structure of ZIF-8 and its size of 150-300 nm. Based on this, porous ZnO and nanoscale In2O3 are derived from ZIF-8. While this technical solution reduces the response time, the sensor material operates at a high temperature of 425℃. This is because In₂O₃ has a stable crystal structure and high carrier mobility; therefore, the catalytic oxidation of hydrogen by In₂O₃ requires a high activation energy, meaning it needs to be at a high temperature to exhibit catalytic activity. Simultaneously, this technical solution aims to lower the potential barrier through the constructed n-type heterojunction. However, at lower temperatures, the resulting material still has a high potential barrier, so the electrons released from the hydrogen reaction are insufficient to significantly lower the barrier, resulting in a weak response. At high temperatures, the carrier concentration in the semiconductor itself increases dramatically, making the heterojunction's potential barrier more "sensitive" to electrons released from the surface reaction, thus generating a large change in resistance. Summary of the Invention
[0006] The purpose of this invention is to provide a tin-zinc bimetallic oxide, its preparation method, and its applications. Addressing the problems of uneven particle size, large average particle diameter, and small specific surface area in existing hydrogen sensing materials, this invention improves upon these issues through the following principles:
[0007] 1. By synergistically interacting tin source and zinc salt with dimethylimidazole at the molecular level to form a metal-organic composite precursor, the uniformity of microstructure is achieved. In subsequent heat treatment, based on the "in-situ symbiosis" mechanism, the free and disordered grain growth and coarsening of each component are effectively suppressed, and finally, uniformly sized nanospheres are obtained.
[0008] 2. By using a simple room temperature solvent method, an n-type semiconductor oxide SnO2 / ZnO is formed. By matching the work function with the band structure, a heterojunction with a moderate barrier height is formed, which can be modulated by hydrogen reaction at a relatively low temperature.
[0009] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:
[0010] A tin-zinc bimetallic oxide is obtained by using tin tetrachloride pentahydrate, zinc nitrate hexahydrate, and dimethylimidazole as raw materials, methanol as solvent, and drying by stirring, centrifugation, and calcination. The tin-zinc bimetallic oxide is abbreviated as Sn-Zn-O.
[0011] The Sn-Zn-O is an n-type semiconductor with a chemical composition of SnO2 and ZnO.
[0012] The Sn-Zn-O has a microstructure of nanospheres with a particle size range of 100-250 nm.
[0013] A method for preparing a tin-zinc bimetallic oxide includes the following steps: First, tin tetrachloride pentahydrate, zinc nitrate hexahydrate, and dimethylimidazole are placed in a methanol solution and stirred. After stirring, the mixture is centrifuged and dried to obtain a precursor. Finally, the precursor is pretreated and calcined to obtain the tin-zinc bimetallic oxide SnO2 / ZnO, abbreviated as Sn-Zn-O.
[0014] The molar ratio of tin tetrachloride pentahydrate, zinc nitrate hexahydrate, and dimethylimidazole is 1:1:4.
[0015] The stirring conditions are: stirring speed of 600-800 rpm and stirring time of 24 h;
[0016] The centrifugation conditions are: centrifugation speed of 5000-8000 rpm and centrifugation time of 5-10 min;
[0017] The drying conditions are: drying temperature of 60-80℃ and drying time of 12-24h;
[0018] The pretreatment conditions are as follows: under nitrogen atmosphere, the heating rate is 2℃ / min, the pretreatment temperature is 250℃, and the pretreatment time is 2h.
[0019] The calcination conditions were as follows: under air conditions, the heating rate was 5℃ / min, the calcination temperature was 500℃, and the calcination time was 2h.
[0020] A method for preparing a Sn-Zn-O based hydrogen sensor involves first mixing and grinding Sn-Zn-O and anhydrous ethanol in a mortar to obtain a slurry; then, uniformly coating the slurry onto a ceramic electrode tube to form a uniform slurry coating; finally, welding the ceramic electrode tube onto a base and attaching a heating wire to obtain the Sn-Zn-O based hydrogen sensor.
[0021] When used as a hydrogen sensor, the optimal operating temperature is 180℃, the response value is 112 at a hydrogen concentration of 1000ppm, the response time is 1.29s, and the recovery time is 147s.
[0022] Within a hydrogen concentration range of 0.1-2000 ppm, it exhibits different responses to different hydrogen concentrations, with the lowest detectable hydrogen concentration being 0.1 ppm.
[0023] The technical effects of this invention have been tested experimentally, and the specific details are as follows:
[0024] XRD and EDS tests showed that Sn-Zn-O contains characteristic peaks of SnO2, and that Sn-Zn-O contains not only Sn and O elements, but also Zn element.
[0025] SEM testing showed that the microstructure of Sn-Zn-O consisted of nanospheres with a particle size range of 100-250 nm. Furthermore, the nanospheres exhibited good dispersibility and a rough surface.
[0026] Hydrogen detection performance tests show that the Sn-Zn-O-based hydrogen sensor performs well in hydrogen concentration detection experiments within a temperature range of 130-230℃. The optimal operating temperature range for the n-type semiconductor Sn-Zn-O is 170-190℃, with a response value of 100-120s. Within a hydrogen concentration range of 0.1-2000ppm, the response value increases with increasing hydrogen concentration, meaning the resistance decreases. Therefore, Sn-Zn-O exhibits different response values for different hydrogen concentrations. The detection limit of Sn-Zn-O is 0.1ppm, with a response time of 1-1.5s and a recovery time of 100-200s, demonstrating rapid response and recovery.
[0027] Based on the above test results, the present invention has the following advantages over the prior art:
[0028] 1. As an n-type semiconductor oxide, Sn-Zn-O sensors have the characteristics of fast response and recovery, low operating temperature, and good long-term stability.
[0029] 2. It can improve the sensitivity of metal oxides to hydrogen without adding precious metals.
[0030] 3. Sn-Zn-O is characterized by low cost, non-toxicity, and environmental friendliness.
[0031] 4. Sn-Zn-O has a low detection limit for hydrogen, which can ensure the safe use of hydrogen and prevent hydrogen leakage. Attached Figure Description
[0032] Figure 1 The image shows the XRD pattern of Sn-Zn-O in Example 1.
[0033] Figure 2 The image shows the EDS diagram of Sn-Zn-O in Example 1;
[0034] Figure 3 The image shows the SEM image of Sn-Zn-O in Example 1.
[0035] Figure 4 The graph shows the response of hydrogen gas of the same concentration to different temperatures in Example 1, Comparative Example 1, and Comparative Example 2.
[0036] Figure 5 The resistance-time variation curves of Sn-Zn-O with different concentrations of hydrogen in Example 1 are shown.
[0037] Figure 6 The curve showing the response recovery time of Sn-Zn-O to low-concentration hydrogen in Example 1;
[0038] Figure 7 The curve of Sn-Zn-O response to hydrogen in Example 1;
[0039] Figure 8 The graph shows the response values of Sn-Zn-O over 30 days in Example 1.
[0040] Figure 9 The image shows the SEM image of Sn-Zn-O-0.5 in Comparative Example 1.
[0041] Figure 10 The image shows the SEM image of Sn-Zn-O-2 in Comparative Example 1. Detailed Implementation
[0042] The present invention will be further described in detail through embodiments and with reference to the accompanying drawings, but this is not intended to limit the scope of the invention.
[0043] Example 1
[0044] A method for preparing a tin-zinc bimetallic oxide, the one-step calcination method includes the following steps: First, tin tetrachloride pentahydrate, zinc nitrate hexahydrate and dimethylimidazole are placed in a methanol solution and stirred under certain conditions. After stirring, the mixture is centrifuged and dried to obtain a precursor. Finally, the precursor is pretreated and calcined under certain conditions to obtain the tin-zinc bimetallic oxide SnO2 / ZnO, abbreviated as Sn-Zn-O.
[0045] The amount of Sn-Zn-O added satisfies the molar ratio of tin tetrachloride pentahydrate, zinc nitrate hexahydrate, and dimethylimidazole as 1:1:4, wherein the molar ratio of tin tetrachloride pentahydrate to zinc nitrate hexahydrate is referred to as the addition ratio.
[0046] The stirring conditions are: stirring speed of 700 rpm and stirring time of 24 h.
[0047] The centrifugation conditions are: centrifugation speed of 6000 rpm and centrifugation time of 6 min; the drying conditions are: drying temperature of 60℃ and drying time of 24 h.
[0048] The pretreatment conditions are as follows: under nitrogen atmosphere, the heating rate is 2℃ / min, the pretreatment temperature is 250℃, and the pretreatment time is 2h.
[0049] The calcination conditions are as follows: under air conditions, the heating rate is 5℃ / min, the calcination temperature is 500℃, and the calcination time is 2h.
[0050] To verify the composition of Sn-Zn-O, XRD tests were performed. The test results are as follows: Figure 1 As shown, Sn-Zn-O only contains characteristic peaks of SnO2, but no characteristic peaks related to Zn were detected. This may be because the tin hydrolysis-condensation process affects the zinc-imidazolium coordination process, resulting in a ZnO content in Sn-Zn-O that is much lower than that of SnO2, thus failing to reach the detection limit and therefore undetectable.
[0051] Therefore, to further verify the composition of Sn-Zn-O, EDS testing was performed. The test results are as follows: Figure 2 As shown, Sn-Zn-O contains not only Sn and O elements, but also Zn element.
[0052] XRD and EDS tests confirm the successful preparation of Sn-Zn-O.
[0053] To demonstrate the microstructure of the Sn-Zn-O oxide, SEM measurements were performed. The results are as follows: Figure 3The microstructure of Sn-Zn-O consists of nanospheres with a particle size range of 100-250 nm. Furthermore, the nanospheres exhibit good dispersibility and a rough surface.
[0054] To demonstrate that Sn-Zn-O has the ability to detect hydrogen, i.e., as a hydrogen sensor, a Sn-Zn-O-based hydrogen sensor was prepared, and hydrogen concentration detection experiments were conducted.
[0055] A method for preparing a Sn-Zn-O based hydrogen sensor involves first mixing and grinding Sn-Zn-O and anhydrous ethanol to obtain a slurry; then, uniformly coating the slurry onto a ceramic electrode tube to form a uniform slurry coating; finally, welding the ceramic electrode tube onto a base and attaching a heating wire to obtain the Sn-Zn-O based hydrogen sensor.
[0056] The basic method for hydrogen concentration detection is to introduce a gas of a given concentration under given temperature and humidity conditions, measure the resistance of Sn-Zn-O, and then calculate the response value.
[0057] The response value is calculated as follows: R a / R g The ratio of R to R a Let R be the initial resistance. g The resistance after the response.
[0058] To demonstrate the hydrogen detection performance of Sn-Zn-O, hydrogen concentration detection experiments were conducted in a temperature range of 130-230℃. Test results... Figure 4 As shown, the optimal operating temperature of Sn-Zn-O is 180℃, and the response value is 112.
[0059] To demonstrate the sensitivity of Sn-Zn-O, hydrogen concentration detection experiments were conducted in a hydrogen concentration range of 50-1000 ppm. The test results are as follows: Figure 5 As shown, the response value of Sn-Zn-O increases with increasing hydrogen concentration, meaning the resistance decreases with increasing hydrogen concentration. The test results indicate that Sn-Zn-O has different response values to different concentrations of hydrogen.
[0060] To further demonstrate the detection limit of Sn-Zn-O, a low-concentration hydrogen gas test was conducted. The test results are as follows: Figure 6 As shown, the detection limit of Sn-Zn-O is 0.1 ppm at an operating temperature of 180℃.
[0061] To demonstrate the response-recovery performance of Sn-Zn-O, response-recovery tests were conducted. The test results are as follows: Figure 7As shown, Sn-Zn-O exhibits a sharp decrease in resistance in a hydrogen atmosphere, displaying characteristics of an n-type semiconductor, with a response time of 1.29 s and a recovery time of 147 s. The test results demonstrate that Sn-Zn-O possesses both fast response and high response value.
[0062] To demonstrate the long-term stability of Sn-Zn-O, multiple response-recovery tests were conducted. Specifically, under operating conditions of 180℃ and a hydrogen concentration of 1000ppm, tests were performed once a week for a total of 8 times, and the test values were recorded.
[0063] Test results are as follows Figure 8 As shown, the response value showed no significant decay. The test results indicate that Sn-Zn-O possesses long-term stability.
[0064] To demonstrate the effect of the metal element addition ratio on performance, Comparative Example 1 and Comparative Example 2 are provided, with Sn-Zn-O prepared at addition ratios of 1:2 and 2:1, respectively.
[0065] Comparative Example 1
[0066] A method for preparing Sn-Zn-O with an addition ratio of 1:2 is provided. The steps, unless otherwise specified, are the same as those in Example 1, except that the addition ratio of tin tetrachloride pentahydrate to zinc nitrate hexahydrate is 1:2. The resulting material is named Sn-Zn-O-0.5.
[0067] To verify the microstructure of Sn-Zn-O-0.5, SEM testing was performed. The test results are as follows. Figure 9 As shown, the microstructure of Sn-Zn-O-0.5 is that of nanospheres, but the particle size ranges from 100 to 1000 nm. Comparison of the test results with Example 1 shows that increasing the proportion of zinc nitrate hexahydrate significantly increases the particle size of some Sn-Zn-O particles, reaching the micrometer level; specifically, this is manifested in a significantly wider particle size distribution range.
[0068] To demonstrate the hydrogen detection performance of Sn-Zn-O-0.5, hydrogen sensing tests were conducted. The test results are as follows: Figure 4 As shown, the optimal operating temperature of Sn-Zn-O-0.5 is 240℃, and the response value is 64. Comparison of the test results with Example 1 shows that increasing the proportion of zinc nitrate hexahydrate leads to both an increase in operating temperature and a decrease in sensitivity.
[0069] As can be seen from Example 1 and Comparative Example 1, increasing the addition ratio of zinc nitrate hexahydrate leads to an increase in particle size, a significant decrease in specific surface area and the number of hydrogen adsorption active sites, and ultimately a significant reduction in hydrogen detection performance.
[0070] Comparative Example 2
[0071] A method for preparing Sn-Zn-O with an addition ratio of 2:1 is provided. The steps, unless otherwise specified, are the same as those in Example 1, except that the addition ratio of tin tetrachloride pentahydrate to zinc nitrate hexahydrate is 2:1. The resulting material is named Sn-Zn-O-2.
[0072] To verify the microstructure of Sn-Zn-O-2, SEM testing was performed. The test results are as follows: Figure 10 As shown, the microstructure of Sn-Zn-O-2 is that of nanospheres, but the particle size ranges from 50 to 100 nm. Comparison of the test results with Example 1 shows that increasing the proportion of tin tetrachloride pentahydrate significantly reduces the particle size of the resulting Sn-Zn-O-.
[0073] To demonstrate the hydrogen detection performance of Sn-Zn-O-2, hydrogen sensing tests were conducted. The test results are as follows: Figure 4 As shown, the optimal operating temperature of Sn-Zn-O-2 is 240℃, and the response value is 48. Comparison of the test results with Example 1 shows that increasing the proportion of tin tetrachloride pentahydrate also leads to both an increase in operating temperature and a decrease in sensitivity.
[0074] As can be seen from Example 1 and Comparative Example 2, increasing the addition ratio of tin tetrachloride pentahydrate leads to a reduction in particle size. Due to the excessively small particle size, the surface energy is significantly increased, resulting in particle agglomeration. The pores inside the agglomerates prevent the diffusion of hydrogen molecules, ultimately leading to a significant reduction in hydrogen detection performance.
Claims
1. A tin-zinc bimetallic oxide characterized by: Sn-Zn-O is obtained by using tin tetrachloride pentahydrate, zinc nitrate hexahydrate and dimethylimidazole as raw materials, methanol as solvent, stirring, centrifugation, drying, and calcination. The Sn-Zn-O is an n-type semiconductor, and the chemical composition is SnO2 and ZnO.
2. The tin-zinc double metal oxide according to claim 1, characterized in that: The micro-morphology of the Sn-Zn-O is nanometer microspheres, and the particle size range is 100-250nm.
3. A process for the preparation of tin-zinc double metal oxides, characterized in that The method comprises the following steps: First, tin tetrachloride pentahydrate, zinc nitrate hexahydrate and dimethylimidazole are placed in a methanol solution for stirring, and after stirring, centrifugation and drying, a precursor is obtained, and finally, the precursor is pretreated and calcined to obtain tin-zinc bimetallic oxide SnO2 / ZnO, which is abbreviated as Sn-Zn-O.
4. The method of claim 3, wherein: The molar ratio of tin tetrachloride pentahydrate, zinc nitrate hexahydrate and dimethylimidazole is 1:1:
4.
5. The method of claim 3, wherein: The stirring condition is that the stirring rate is 600-800rpm, and the stirring time is 12-24h. The centrifugation condition is that the centrifugation speed is 5000-8000rpm, and the centrifugation time is 5-10min. The drying condition is that the drying temperature is 60-80℃, and the drying time is 12-24h.
6. The method of claim 3, wherein: The pretreatment condition is that the temperature rising rate is 2℃ / min under nitrogen condition, the pretreatment temperature is 250℃, and the pretreatment time is 2h. The calcination condition is that the temperature rising rate is 5℃ / min under air condition, the calcination temperature is 500℃, and the calcination time is 2h.
7. A method for producing a Sn-Zn-O-based hydrogen sensor, characterized by: First, Sn-Zn-O and anhydrous ethanol are placed in a mortar for mixing and grinding to obtain a slurry; then, the slurry is uniformly coated on a ceramic electrode tube to form a uniform slurry coating; finally, the ceramic electrode tube is welded on a base, and a heating wire is welded thereon to obtain a hydrogen sensor based on Sn-Zn-O.
8. The sensor fabrication method of claim 7, wherein: When Sn-Zn-O is used as a hydrogen sensor, the optimal working temperature range is 170-190℃, the response value under a hydrogen concentration of 1000ppm is 100-120, the response time is 1-1.5s, and the recovery time is 100-200s; Under a hydrogen concentration range of 0.1-2000ppm, different concentrations of hydrogen have different responses, and the lowest hydrogen concentration detection is 0.1ppm.